Clients’ experiences of HIV positive status disclosure to sexual partners at St Rita’s hospital, Limpopo Province, South Africa - Mamogobo, P. M.; Lekhuleni, M. E.; Matlala, S. F. (Department of Nursing Science, University of Limpopo, 2013)
Abstract The purpose of the study was to describe the experiences of HIV positive clients as they disclose their HIV positive status to their sexual partners. A qualitative descriptive and phenomenological design was used. Purposive sampling was used to select 15 HIV positive clients to participate in the study. Semi-structured interviews were used to collect data until saturation was reached. Data analysis was done using Techs open coding method. The study revealed problems of disclosure related to rejection or acceptance of HIV positive status, precipitating factors towards HIV infection transmission and consequences of HIV positive status such as fear of losing a partner. The study recommended health education campaigns on disclosure of HIV positive status and awareness campaigns regarding coping with HIV positive status and disclosure. Keywords: Disclosure, HIV positive, AIDS, experiences, sexual partner.
Published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD), March 2013 (Supplement 1), pp. 35-47.
Keywords: Disclosure; HIV positive; AIDS; Sexual partners; HIV-positive persons; Self-disclosure - Testing; Disclosure